Tidal modulations of mesospheric gravity wave kinetic energy observed with MF radar at Poker Flat Research Range, Alaska. Issue 13 (14th July 2015) - Kinoshita, Takenari; Murayama, Yasuhiro; Kawamura, Seiji
Abstract The interactions between gravity waves and atmospheric tidal waves have been observationally studied, although the phase relation between them has not been fully understood. In this study, the long‐term wind velocity data observed with the Poker Flat MF radar (65∘N, 147∘W) were analyzed for the period of 1999–2008 to show local time dependence and seasonal climatologies of the 12 h and 24 h components in the mesospheric winds and their modulations of gravity wave kinetic energy. We made climatological 1 day composite plots of the kinetic energy of gravity waves for wave periods of 1–4 h and harmonic components of horizontal wind for each month. The results show that the kinetic energy of gravity waves peaks twice at 3–6 LT and 18–21 LT, which tend to coincide with the transition of the 12 h component of zonal wind from westward to eastward flow. On the other hand, a 2 month case study revealed that the gravity wave kinetic energy and the 12 h components of zonal wind appear to keep their phase difference constant (like a "phase locked") for more than 10 days. Events of this kind are also found in other years. To examine whether this relation can be explained by interaction between the 12 h component of zonal wind and gravity waves, we applied a gravity wave drag model to the background state defined as the sum of observed monthly mean and harmonic components of zonal wind. It is suggested that the orographic gravity wave drag has a 12 h periodicity and that the time of the drag enhancement changes in time following change in the phase of harmonic components of winds.